Anxiety and depression in the pandemic: assessment of the mental health of medical students: Ansiedade e depressão em estudantes de medicina - Silva Correa Reis, Giovana; de Melo e Silva, Andrícia de Jesus; Santos dos Santos, Mainã Cristina; Marcela dos Santos Lopes, Andrea; Regina Bastos Neder, Patrícia (Journal of Health Care, 2024)
In recent years, there has been a considerable increase in the prevalence of mental disorders, especially among medical students. OBJECTIVE: With the pandemic caused by Sars-CoV-2 virus and the changes brought by it, there was a need to identify the prevalence of symptoms of depression and anxiety in medical students in a university in Northern Brazil during this period. METHODS: An observational, descriptive, cross-sectional study carried out with 240 medical students during the second wave of the COVID-19 pandemic. A validated questionnaire applied with Google Forms in order to assess and classify symptoms of depression and anxiety. The chi-square test was used to assess correlations. RESULTS: the study observed that the majority of the students had no symptoms of anxiety and depression; however, among those who did, 14.9% of women had severe anxiety. It was seen that there was no significant association between age and the presence of symptoms of mental disorder, and it was observed that symptoms of anxiety and depression were most reported in first, second and fourth year students. CONCLUSIONS: The research participants had mild levels of anxiety and depression, differing from most scientific studies. It was noticed that there was a higher prevalence of moderate to severe symptoms of anxiety in the female population and of depression in the male population. The most affected age was 23 years, in first and fourth year students.